Reversible Watermarking Based on Sorting Prediction Scheme - Fakhreldin, Mohammed Adam Ibrahim; Khalid, Edris; Jasni, Mohamad Zain; Tuty Asmawaty, Abdul Kadir; Khalid, Adam (IEEE Xplore® digital library, 2014)
Reversible watermarking has drawn a lot of interest in recent years. To be reversible mean the original digital carrier can be completely restored. Sachnev et al proposed reversible watermarking algorithm by combining prediction technology, histogram shifting technology and sorting technology, which has good performance, however, their method is against the characteristics of the human visual system. In this paper, we propose a reversible watermarking algorithm to improve Sachnev et al algorithm by using new sorting method. The performance of the proposed reversible watermarking algorithm is evaluated and compared with Sachnev et al method. The results indicate that the proposed scheme can embed data with less distortion.